Influence of Magnetic Treated Saline Water on Salts Leaching from Salt Affected Soil - Hassan, Khalida Abdul-Karim; Hashim, Farhad Ali; Ahmed, Sarwar Mohammed Rasheed (Sulaimani Journal for Pure and Applied Sciences, 2016)
To investigate the effect of water magnetic treatment and irrigation water salinity on salt leaching from salt affected soil (40.13dS m -1 ), a laboratory experiment was conducted using soil columns filled with salt affected soil and leached by using 5 and 10 dS m -1 saline water and fresh water (control,1.56 dS m -1 ). The results showed a remarkable decrease in EC values under all treatments. Concentrations of Na, Ca and Mg decrease with increasing the number of pore volumes. The efficiency of magnetic treatment on leaching soluble salts from soil is higher when using water of low salinity in comparison with water of high salinity level.
Keywords: Magnetic Water; Water Salinity; Leaching